Energy harvesting from a DE-based dynamic vibro-impact system. (30th August 2017) - Yurchenko, D; Val, D V; Lai, Z H; Gu, G; Thomson, G
Abstract: Dielectric elastomer (DE) generators may be used in harvesting energy from ambient vibrations. Based on existing research on the mechanical properties of a circular DE membrane, a DE-based dynamic vibro-impact system is proposed in this paper to convert vibrational energy into electrical one. The dimensional, electrical and dynamic parameters of the DE membrane are analysed and then used to numerically estimate the output voltage of the proposed system. The system output performances under harmonic excitation are further discussed. At last, the comparison study has been conducted with an electromagnetic energy harvesting system, served as a 'shaking' flashlight.